Racial and Socioeconomic Disparities in Prompt Craniosynostosis Workup and Treatment. Issue 8 (29th November 2022) - Badiee, Ryan K.; Maru, Johsias; Yang, Stephen C.; Alcon, Andre; Rosenbluth, Glenn; Pomerantz, Jason H.
Abstract : The purpose of this study was to identify racial and socioeconomic disparities in craniosynostosis evaluation and treatment, from referral to surgery. Patients diagnosed with craniosynostosis between 2012 and 2020 at a single center were identified. Chart review was used to collect demographic variables, age at referral to craniofacial care, age at diagnosis, age at surgery, and surgical technique (open versus limited incision). Multivariable linear and logistic regression models with lasso regularization assessed the independent effect of each variable. A total of 298 patients were included. Medicaid insurance was independently associated with a delay in referral of 83 days [95% confidence interval (CI) 4–161, P =0.04]. After referral, patients were diagnosed a median of 21 days later (interquartile range 7–40), though this was significantly prolonged in patients who were not White (β 23 d, 95% CI 9–38, P =0.002), had coronal synostosis (β 24 d, 95% CI 2–46, P =0.03), and had multiple suture synostosis (β 47 d, 95% CI 27–67, P <0.001). Medicaid insurance was also independently associated with diagnosis over 3 months of age (risk ratio 1.3, 95% CI 1.1–1.4, P =0.002) and undergoing surgery over 1 year of age (risk ratio 3.9, 95% CI 1.1–9.4, P =0.04). In conclusion, Medicaid insurance was associated with a 3-month delay in referral to craniofacial specialists and increased risk of diagnosis over 3 months of age, limiting surgical treatment options in this group. Patients with Medicaid also faced a 4-fold greater risk of delayed surgery, which could result in neurodevelopmental sequelae.